ANALYSIS OF SMK KRISTEN 1 SURAKARTA PERFORMANCE WITH THE BALANCE SCORECARD APPROACH - P Haryoso; Christiyanto Indra Pamungkas (STIE AUB Surakarta, 2019)
The purpose of this study is to measure the performance of the SMK Kristen 1 Surakarta with four perspectives in the Balance Scorecard, namely financial, customer, internal business processes and growth and learning perspectives. This study uses quantitative descriptive research. The population in this study amounted to 425 people who were sampled using purposive sampling technique and obtained a sample of 30 people. The data analysis technique used is descriptive statistics. The results of the study show that the financial perspective has an overall score of 14 from a total score of 15 meaning that the excellent performance shows that it is very economical, very efficient and effective. The results of the performance measurement of the perspective of the customer of the Christian 1 Surakarta Vocational High School get a score of 4 from a total score of 5 which means good performance. The results of the measurement of internal business process perspective score 40 from a total score of 50 showing good performance. The results of the growth and learning perspective measurements get a score of 5 from totak score of 5 means that the performance is very good.